O tempo-espaço em Ismália: o livro-objeto como aparelho técnico - Tosta, Lion Santiago (2021)
The aim of this dissertation is to analyze the time and space in Ismália, by Odilon Moraes and Alphonsus de Guimaraes (2006), understanding that the location and interpretation of these aspects contribute to the criticism about the book-object and, consequently, allows it to be observed and configures it as a technical apparatus of post- modernity. The book Ismália was chosen to trace this path because it is an book-object that articulates languages with great efficiency. To weave the corpus analysis, we mobilize the concept of time Kairós, based on the studies of Giorgio Agamben (2016), and the concept of the method of montage in the perspective of Georges Didi-Huberman (2017, 2018), both founded and based on the intersection of Walter Benjamin’s thoughts. In the same direction, it is intended to understand how the book-object, in its language experimentation (Agamben, 2018 and Palo, 2019), sparks a passage to a threshold zone (Benjamin, 2007 and Behrens, 2010) where the Voice can be accessed (Agamben, 2006 and Palo), which makes it possible to understand the literary corpus of this research as a technical apparatus (Flusser, 2008, 2018). Authors and critics of the book (Mellot 2012) and the book-object (Coats, 2008 and Linden, 2001), are also mobilized, in addition to the critical fortune of the poem and the book analyzed in the dissertation (O’hara, 2014 and Navas e Ramos, 2020). The objective of this research is to expand the critical understanding about the concept of book-object, pointing out how the experimentation of articulated language in Ismália amplifies the thought of the analysis of the book-object as a technical apparatus capable of promoting an effective aesthetic transformation in literature